Assessing the MR compatibility of dental retainer wires at 7 Tesla. Issue 4 (11th November 2013) - Wezel, Joep; Kooij, Bert Jan; Webb, Andrew G.
<x xml:space="preserve">Abstract</x> Purpose To determine the MR compatibility of common dental retainer wires at 7 Tesla in terms of potential RF heating and magnetic susceptibility effects. Methods Electromagnetic simulations and experimental results were compared for dental retainer wires placed in tissue‐mimicking phantoms. Simulations were then performed for a human model with wire in place. Finally, image quality was assessed for different scanning protocols and wires. Results Simulations and experimental data in phantoms agreed well, with the length of the wire correlating to maximum heating in phantoms being approximately 47 mm. Even in this case, no substantial heating occurs when scanning within the specific absorption rate (SAR) guidelines for the head. Image distortions from the most ferromagnetic dental wire were not significant for any brain region. Conclusion Dental retainer wires appear to be MR compatible at 7 Tesla. Magn Reson Med 72:1191–1198, 2014. © 2013 Wiley Periodicals, Inc.